97.7k views
5 votes
Calculate the limit values:

a) lim
   x → ∞ ln (x ^ 2 + 2) / x

  b) lim
      x → 0 tan x / x

c) lim
    x → 0 e 2x - 1 - 2x / x 2 2

d) lim
     x → ∞? (√x ^ 2 + 2x - x)

User Mirka
by
6.3k points

1 Answer

6 votes
a) This particular limit is of the indeterminate form,

( \infty )/( \infty )
if we plug in infinity directly, though it is not a number just to check.

If a limit is in this form, we apply L'Hopital's Rule.

's

Lim_(x \rightarrow \infty ) ( ln(x ^(2) + 1 ) )/(x) = Lim_ {x \rightarrow \infty } (( ln(x ^(2) + 1 ) ) ')/(x ' )
So we take the derivatives and obtain,


Lim_ {x \rightarrow \infty } ( ln(x ^(2) + 1 ) )/(x) = Lim_(x \rightarrow \infty ) ( (2x)/(x^(2) + 1) )/(1)

Still it is of the same indeterminate form, so we apply the rule again,


Lim_(x \rightarrow \infty ) ( ln(x ^(2) + 1 ) )/(x) = Lim_(x \rightarrow \infty ) ( 2 )/(2x)

This simplifies to,


Lim_(x \rightarrow \infty ) ( ln(x ^(2) + 1 ) )/(x) = Lim_(x \rightarrow \infty ) ( 1 )/(x) = 0

b) This limit is also of the indeterminate form,


(0)/(0)
we still apply the L'Hopital's Rule,


Lim_ {x \rightarrow0 }( tanx)/(x) = Lim_ {x \rightarrow0 } ( (tanx)')/(x ' )


Lim_ {x \rightarrow0 }( tanx)/(x) = Lim_ {x \rightarrow0 } ( \sec ^(2) (x) )/(1 )

When we plug in zero now we obtain,


Lim_ {x \rightarrow0 }( tanx)/(x) = Lim_ {x \rightarrow0 } ( \sec ^(2) (0) )/(1 ) = (1)/(1) = 1
c) This also in the same indeterminate form


Lim_ {x \rightarrow0 }\frac{ {e}^(2x) - 1 - 2x}{ {x}^(2) } = Lim_ {x \rightarrow0 } \frac{ ({e}^(2x) - 1 - 2x)'}{( {x}^(2) ) ' }


Lim_ {x \rightarrow0 }\frac{ {e}^(2x) - 1 - 2x}{ {x}^(2) } = Lim_ {x \rightarrow0 } \frac{ (2{e}^(2x) - 2)}{ 2x }

It is still of that indeterminate form so we apply the rule again, to obtain;


Lim_ {x \rightarrow0 }\frac{ {e}^(2x) - 1 - 2x}{ {x}^(2) } = Lim_ {x \rightarrow0 } \frac{ (4{e}^(2x) )}{ 2 }

Now we have remove the discontinuity, we can evaluate the limit now, plugging in zero to obtain;


Lim_ {x \rightarrow0 }\frac{ {e}^(2x) - 1 - 2x}{ {x}^(2) } = \frac{ (4{e}^(2(0)) )}{ 2 }

This gives us;


Lim_ {x \rightarrow0 }\frac{ {e}^(2x) - 1 - 2x}{ {x}^(2) } =( (4(1) ))/( 2 )=2

d)
Lim_ {x \rightarrow +\infty }√(x^2+2x)-x

For this kind of question we need to rationalize the radical function, to obtain;


Lim_ {x \rightarrow +\infty }(2x)/(√(x^2+2x)+x)

We now divide both the numerator and denominator by x, to obtain,


Lim_ {x \rightarrow +\infty }\frac{2}{\sqrt{1+(2)/(x)}+1}

This simplifies to,


=(2)/(√(1+0)+1)=1
User Mahmoud Maghrabi
by
5.0k points